Ritual Amoek Melayu: Rekonstruksi atas Ritus-ritus Kekerasan di Indonesia - Dwipayana, AAGN Ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2001)
The display of violence is needed by the rulers who need to ensure that its power relationship is unchallenged. By using the same logic the ruled also having potential of expressing violence. Such an expressioni is called amoek.